Some Aspects of Documentary Narration in 20th Century Fiction - Kobiashvili, Maia ("Intercultural Dialogues" Transactions, 2025)
The public's lively interest in Soviet literary processes has not waned to this day, which is a clear challenge for critics to fundamentally analyze how the reality of Sovietization was reflected in works of fiction. In terms of national identity, Georgian society is characterized by ambiguity. They have the same desire and goal, but in their pursuit of the goal, they move in a stream, stop, move, stop, and sometimes deviate from the path. This process is determined by political, historical, and geographical factors. The joy of the independent Georgian flag as a symbol of national identity was replaced by the Soviet red flag as a new ideological relic. The most severe was the destruction of the achievements of 1918. The tragedy of 1921 gave rise to two main currents in literature: the writers who were in favor of Sovietization, or proletarian writing, and the disillusioned writers who were deprived of creative freedom by the regime. Special importance should be given to writing created with documentary accuracy, with a slight hint of feelings, emotions, and artistry. In this paper, we will focus on Nikolo Mitsishvili's documentary prose "February", Konstantine Gamsakhurdia's short story "Great Joseph", and Kolau Nadiradze's poem "February 25, 1921". Mitsishvili's work is significantly distinguished by its documentary nature. He even has an article titled "Documentary Prose," in which he expresses the position that the contemporary situation forces writers to write only about real, unadorned life, because, in his own words, "a true story is better than a fictional story." Although the documentary genre has still not gained a foothold in our country, it is worth noting that its attempt is associated with the name of Nikolo Mitsishvili. Undisguisedly conveying historical reality in literature and writing is a great risk and courage, but it is extremely important, like a lullaby for a baby or a fairy tale for a child, because words affect people like a bomb and drag them into their bosom. The general reader should perceive the narrative discussed here as lessons from the past and connect history to the challenges of contemporary life.